Sustained in vivo perfusion of a re-endothelialized tissue engineered kidney graft in a human-scale animal model - Uzarski, Joseph S.; Beck, Emily C.; Russell, Emily E.; Vanderslice, Ethan J.; Holzner, Matthew L.; Wadhera, Vikram; Adamson, Dylan; Shapiro, Ron; Davidow, Dominique S.; Ross, Jeff J.; Florman, Sander S. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Despite progress in whole-organ decellularization and recellularization, maintaining long-term perfusion in vivo remains a hurdle to realizing clinical translation of bioengineered kidney grafts. The objectives for the present study were to define a threshold glucose consumption rate (GCR) that could be used to predict in vivo graft hemocompatibility and utilize this threshold to assess the in vivo performance of clinically relevant decellularized porcine kidney grafts recellularized with human umbilical vein endothelial cells (HUVECs). Materials and Methods: Twenty-two porcine kidneys were decellularized and 19 were re-endothelialized using HUVECs. Functional revascularization of control decellularized (n=3) and re-endothelialized porcine kidneys (n=16) was tested using an ex vivo porcine blood flow model to define an appropriate metabolic glucose consumption rate (GCR) threshold above which would sustain patent blood flow. Re-endothelialized grafts (n=9) were then transplanted into immunosuppressed pigs with perfusion measured using angiography post-implant and on days 3 and 7 with 3 native kidneys used as controls. Patent recellularized kidney grafts underwent histological analysis following explant. Results: The glucose consumption rate of recellularized kidney grafts reached a peak of 39.9±9.7 mg/hour at 21±5 days, at which point the grafts were determined to have sufficient histological vascular coverage with endothelial cells. Based on these results, a minimum glucose consumption rate threshold of 20 mg/hour was set. The revascularized kidneys had a mean perfusion percentage of 87.7±10.3%, 80.9±33.1%, and 68.5±38.6% post-reperfusion on Days 0, 3 and 7, respectively. The 3 native kidneys had a mean post-perfusion percentage of 98.4±1.6%. These results were not statistically significant. Conclusion: This study is the first to demonstrate that human-scale bioengineered porcine kidney grafts developed via perfusion decellularization and subsequent re-endothelialization using HUVEC can maintain patency with consistent blood flow for up to 7 days in vivo. These results lay the foundation for future research to produce human-scale recellularized kidney grafts for transplantation.